Clash of corporate governance logics obscuring auditor independence. Issue 2 (18th July 2019) - Eklöv Alander, Gunilla
Abstract : Audit committees are regarded by regulators as beneficial for improving audit independence and are hence globally enforced. This study aligns with research that questions whether audit committees function well in nations that differ from the Anglo‐Saxon model. The aim of the study is to examine if the auditor and audit committee relationship conforms with a Swedish or Anglo‐Saxon logic, and to analyze the impact on auditor independence. A critical discourse analysis is undertaken on corporate governance reports and three dimensions of logics are found: one complying with Swedish logic (compliance) and two according to Anglo‐Saxon logic (varieties of subordination). The study indicates that the discourse on audit committees following an Anglo‐Saxon logic in this national setting constructs a power relation with the auditor that hampers the auditor's independence, and hence, that auditor independence is context bound. The importance of the composition of the audit committee and its members independence also from larger owners is discussed. The study contributes to research that marks the importance of a better understanding of national jurisdictions before international harmonization can be achieved.